Trehalose limits BSA aggregation in spray‐dried formulations at high temperatures: Implications in preparing polymer implants for long‐term protein delivery. Issue 8 (10th June 2013) - Rajagopal, Karthikan; Wood, Joseph; Tran, Benjamin; Patapoff, Thomas W.; Nivaggioli, Thierry
Abstract: Polymer implants are promising systems for sustained release applications but their utility for protein delivery has been hindered because of concerns over drug stability at elevated temperatures required for processing. Using bovine serum albumin (BSA) as a model, we have assessed whether proteins can be formulated for processing at elevated temperatures. Specifically, the effect of trehalose and histidine‐HCl buffer on BSA stability in a spray‐dried formulation has been investigated at temperatures ranging from 80°C to 110°C. When both the sugar and buffer are present, aggregation is suppressed even when exposed to 100°C, the extrusion temperature of poly(lactide‐co‐glycolide) (PLGA), a bioresorbable polymer. Estimation of aggregation rate constants ( k ) indicate that though both trehalose and histidine‐HCl buffer contribute to BSA stability, the effect because of trehalose alone is more pronounced. BSA‐loaded PLGA implants were prepared using hot‐melt extrusion process and in vitro release was conducted in phosphate buffered saline at 37°C. Comparison of drug released from implants prepared using four different formulations confirmed that maximal release was achieved from the formulation in which BSA was least aggregated. These studies demonstrate that when trehalose and histidine‐HCl buffer are included in spray‐dried formulations, BSA stability is maintained both during processing at 100°C and long‐term residence within implants. © 2013 Wiley Periodicals, Inc. and the American Pharmacists Association J Pharm Sci 102:2655–2666, 2013